Correlation of fatty acid composition of adipose tissue lipids and serum phosphatidylcholine and serum concentrations of micronutrients with disease duration in rheumatoid arthritis. Issue 11 (November 1990) - Jacobsson, L; Lindgärde, F; Manthorpe, R; Akesson, B
Abstract : To establish the concentrations of micronutrients in serum, fatty acid composition in serum phosphatidylcholine and in adipose tissue, and their correlation with inflammation and disease duration in rheumatoid arthritis (RA), 21 consecutive patients with recently diagnosed disease (mean duration eight months), 21 patients with longstanding disease (mean duration 15 years), and 57 controls were examined. In the patients with RA low concentrations of the essential fatty acids, linoleic acid (18:2) and linolenic (18:3) acid, and high concentrations of total saturated fatty acids, both in serum phosphatidylcholine and in adipose tissue, were found, abnormalities that increased with disease duration. The proportion of 18:2 in serum phosphatidylcholine correlated inversely with such acute phase proteins as orosomucoid and C reactive protein. It is proposed that the decreases in essential fatty acids are related to increased activity in the desaturase/elongation enzymes, increased production of eicosanoids, or metabolic changes secondary to cytokine mediated inflammatory reaction. When the micronutrients were studied it was found that serum concentrations of selenium were lower in patients than in controls, but not those of ascorbic acid, alpha-tocopherol, retinol, folic acid, or cobalamine. Ascorbic acid concentrations tended to be lower in RA, however, and correlated inversely with those of haptoglobin, orosomucoid, and C reactive protein, indicating a relation between the ascorbic acid concentration and the degree of inflammation.